A system and method of language translation - Abdul Aziz, Normaziah; Suhaimi, Ab Rahman (2008)
The present invention generally relates to a system to translate a language automatically wherein a hardware such as a computer is used in the system . The system comprises of sentence level and a phrase look up matching technique and wherein the present invention searchers a translation memory to find out whetehr there are closely matched examples and sentence level matching technique. When a record is found , the translation technique would return the translation suggestion for the input sentence and where no more records are matched, then a phrase look up matching technique is applied and wherein further to this a bi -section technique would analyze an input sentence by splitting it into two different parts and wherein a first part is from the first word until a splitting point and the second part is to hold the rest of the word/sentence adn wherein the longest chunk for the input sentence is searched starting movement from the left portion of th word to the right portion of the word and wherein after obtaining an output from the first part of the original phrase, the second part will act as the original phrase and it will be split further.